Voluntary adoption of environmental standards and limited attention: Evidence from the food and beverage industry in Vietnam - Massimo Filippini; Suchita Srinivasan (ETH Zurich, CER-ETH - Center of Economic Research, 2020)
Voluntary approaches to environmental policy can contribute to stemming environmental degradation in developing countries with weak institutions. We evaluate the role of a behavioral anomaly, limited attention paid by owners or managers, in explaining the voluntary adoption of environmental certification by small and medium enterprises (SMEs) in the food and beverage industry in Vietnam. We find that firms where owners or managers were inattentive were 30 percentage points less likely to receive environmental certification. Moreover, this effect is larger for firms that were previously inspected for technical violations, and that exported or bribed, and it is weaker for household enterprises.
Keywords: D22; D83; D91; O13; Q56; Q59; 330; Voluntary environmental standards; Limited attention; Small and medium enterprises; Food and beverage industry; Vietnam